(untitled) (Journal of Rangpur Medical College, 2023)
Background: Overweight and obesity has been announced as a global epidemic by The World Health Organization. These conditions have strong associations with renal function impairment. Objectives: To evaluate the estimated glomerular filtration rate (eGFR) in obese male adults and to observe the correlation of eGFR with body mass index (BMI). Methods: This cross-sectional analytical study was conducted at the Department of Physiology, Rangpur Medical College, Rangpur. After briefing about objectives, adult males who met the inclusion and exclusion criteria were enrolled in the study by consensus. The study involved 60 people who were divided into two groups: apparently healthy adult males of average weight (Group A) and apparently healthy adult males who were obese (Group B). The subjects were selected from different districts of the city of Rangpur. Their body mass index & serum creatinine were measured. eGFR was calculated by Cockcroft-Gault equation using serum creatinine. For statistical analysis, unpaired t-test and Pearson’s correlation coefficient test were performed as applicable by computer-based SPSS–25.0 for windows. Regarding the interpretation of results, p≤0.05 was accepted as significant. Results: The mean of estimated glomerular filtration rate was significantly (p≤ 0.001) lower in obese male adults than in normal-weight male adults. This study also found a highly significant (p≤0.05) negative correlation of eGFR (r = -0.317) with body mass index. Conclusion: eGFR is reduced in obese male adults, and it is negatively correlated with BMI. Regular body mass index screening is recommended as an easy and effective means of assessing body weight. J Rang Med Col. March 2023; Vol. 8, No. 2:27-32